Increasing Veno-Arterial Extracorporeal Membrane Oxygenation Flow Reduces Electrical Impedance of the Lung Regions in Porcine Acute Heart Failure - Popková, M; Kuriščák, E; Hála, P; Janák, D; Tejkl, L; Bělohlávek, J; Ošťádal, P; Neužil, P; Kittnar, O; Mlček, M (Physiological research, 2020)
Veno-arterial extracorporeal membrane oxygenation (VA ECMO) is a technique used in patients with severe heart failure. The aim of this study was to evaluate its effects on left ventricular afterload and fluid accumulation in lungs with electrical impedance tomography (EIT). In eight swine, incremental increases of extracorporeal blood flow (EBF) were applied before and after the induction of ischemic heart failure. Hemodynamic parameters were continuously recorded and computational analysis of EIT was used to determine lung fluid accumulation. With an increase in EBF from 1 to 4 l/min in acute heart failure the associated increase of arterial pressure (raised by 44%) was accompanied with significant decrease of electrical impedance of lung regions. Increasing EBF in healthy circulation did not cause lung impedance changes. Our findings indicate that in severe heart failure EIT may reflect fluid accumulation in lungs due to increasing EBF.
Keywords: Animals; koronární cirkulace; Extracorporeal Membrane Oxygenation; mimotělní membránová oxygenace; Female; Lung; ženské pohlaví; Heart Failure; Hemodynamics; hemodynamika; srdeční selhání; prasata; Respiratory Insufficiency; Coronary Circulation; elektrická impedance; modely nemocí na zvířatech; Swine; Disease Models, Animal; plíce; zvířata; Electric Impedance; respirační insuficience